Analysis of one million base pairs of Neanderthal DNA - Green, Richard E.; Krause, Johannes; Ptak, Susan E.; Briggs, Adrian W.; Ronan, Michael T.; Simons, Jan F.; Du, Lei; Egholm, Michael; Rothberg, Jonathan M.; Paunovic, Maja; Pääbo, Svante (Nature, 2006)
Neanderthals are the extinct hominid group most closely related to contemporary humans, so their genome offers a unique opportunity to identify genetic changes specific to anatomically fully modern humans. We have identified a 38,000-year-old Neanderthal fossil that is exceptionally free of contamination from modern human DNA. Direct high-throughput sequencing of a DNA extract from this fossil has thus far yielded over one million base pairs of hominoid nuclear DNA sequences. Comparison with the human and chimpanzee genomes reveals that modern human and Neanderthal DNA sequences diverged on average about 500,000 years ago. Existing technology and fossil resources are now sufficient to initiate a Neanderthal genome-sequencing effort. Neanderthal Genomics Neanderthal traits appear in the human fossil record of Europe and western Asia about 400,000 years ago and vanish about 30,000 years ago. The Neanderthals are our closest extinct relatives, so as DNA technology advances the tantalizing prospect of identifying genetic changes characteristic of fully modern humans comes closer. A 38,000-year-old Neanderthal bone of sufficiently high quality to allow the extraction of more than a million base pairs has now been identified: it was originally found Vindija cave in Croatia (pictured on the cover) in 1980. Comparison of its DNA with the chimp and human genomes reveals that Neanderthal and human ancestors — like humans but unlike apes — had a small effective population size. The technology used in this work offers the prospect of a draft Neanderthal genome within two years.